2001
DOI: 10.1152/ajpregu.2001.280.4.r994
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of angiotensin-(1–7)-induced inhibition of angiogenesis

Abstract: Angiotensin-(1-7) [ANG-(1-7)], an endogenous bioactive peptide constituent of the renin-angiotensin system, acts as an inhibitory growth factor in vitro and in vivo. In this study, we evaluated whether the antiangiogenic effect of ANG-(1-7) in the mouse sponge model of angiogenesis might be receptor mediated and involved in the release of nitric oxide (NO). The hemoglobin content (microg/mg wet tissue) of 7-day-old sponge implants was used as an index of the vascularization and showed that daily injections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 38 publications
6
61
1
Order By: Relevance
“…Antiangiogenic properties of Ang-(1-7), first described by Machado et al, 58,59 and those reported by us on protein synthesis 35,60 endow this peptide with antitumoral properties since Gallagher and Tallant 61 showed that Ang-(1-7) inhibits growth in 3 human lung cancer cell lines (human adenocarcinoma SK-LU-1, A549 cells, and non-small lung cancer SK-MES-1 cells). Treatment with Ang-(1-7) resulted in both a dose-and time-dependent reduction in serum-stimulated DNA synthesis in all 3 of the cell lines, with an IC 50 in the subnanomolar range.…”
Section: An Additional Perspectivementioning
confidence: 87%
“…Antiangiogenic properties of Ang-(1-7), first described by Machado et al, 58,59 and those reported by us on protein synthesis 35,60 endow this peptide with antitumoral properties since Gallagher and Tallant 61 showed that Ang-(1-7) inhibits growth in 3 human lung cancer cell lines (human adenocarcinoma SK-LU-1, A549 cells, and non-small lung cancer SK-MES-1 cells). Treatment with Ang-(1-7) resulted in both a dose-and time-dependent reduction in serum-stimulated DNA synthesis in all 3 of the cell lines, with an IC 50 in the subnanomolar range.…”
Section: An Additional Perspectivementioning
confidence: 87%
“…Studies from our laboratory documented that ANG-(1-7) reverses neointimal growth induced by denudation of the vascular endothelium of a carotid artery (29) through a non-AT 1 /AT 2 receptor (16). Additional antiangiogenic effects of ANG-(1-7) were documented in a mouse sponge model of angiogenesis, whereby ANG-(1-7) inhibited vessel formation within the implant (24,25). There is evidence that ANG-(1-7) contributes to the antihypertensive effect produced by blockers of the RAS because blockade of ANG-(1-7) receptors with a selective receptor antagonist or a selective ANG-(1-7) antibody reversed the antihypertensive effect mediated by chronic administration of lisinopril and losartan in rats (22).…”
Section: Discussionmentioning
confidence: 97%
“…There was evidence suggesting that the AT 2 receptor mediates ANG-(1-7)-induced relaxation of porcine coronary arteries associated with NO and kinins (Gorelik et al, 1998). It was suggested that the antiangiogenic effect of ANG-(1-7) in the mouse sponge model of angiogenesis is associated with NO release by activation of an ANG receptor distinct from AT 1 and AT 2 (Machado et al, 2001). In preexisting (skin) and newly formed vasculature (14-day-old polyurethane sponge implants) in mice, ANG-(1-7)-induced vasodilator effects was prevented by the specific receptor antagonist (D-Ala 7 )-ANG-(1-7) and abolished by NOS inhibitors, suggesting that this peptide contributes to the vasodilatation via NO also in newly formed vascular beds (Machado et al, 2002).…”
Section: Angiotensin-(1-7)-induced Vasodilatationmentioning
confidence: 99%